Effect of Learning Environment and Social Support On Co-Curricular: Mediation of Academic Enrichment and Self-Efficacy - Betha Wijayanti; Wilis Werdiningsih; Mohd Syaubari Othman (Jurnal Educative: Journal of Educational Studies, 2025)
Students’ co-curricular achievement has not received sufficient attention in school development, even though learning environment resources and social support play essential roles in shaping student participation. Limited use of facilities and inconsistent support often reduce involvement in academic enrichment activities and weaken self-efficacy. This study examines the mediating roles of educational enrichment and self-efficacy in the influence of learning environmental resources and social support on students’ co-curricular achievement. A quantitative survey was conducted with 78 students at SMAN 2 Ponorogo. Data was collected using a four-point Likert questionnaire with five variables and 28 indicators, then analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test seven direct and five indirect relationships. The results show that learning environmental resources and social support positively and significantly influence co-curricular achievement, both directly and through the mediation of academic enrichment and self-efficacy. Academic enrichment links learning resources to performance, while self-efficacy strongly mediates the influence of social support. These findings highlight the need to strengthen enrichment programs and confidence-building strategies within school initiatives. This study contributes a comprehensive PLS-SEM model integrating environmental and psychosocial factors, offering clearer insight into how these elements collectively shape students’ co-curricular achievement.